1996
DOI: 10.1021/jm9506581
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship Studies of Novel 4-[2-[Bis(4-fluorophenyl)methoxy]ethyl]-1-(3-phenylpropyl)piperidine Analogs:  Synthesis and Biological Evaluation at the Dopamine and Serotonin Transporter Sites

Abstract: Several analogs of the potent dopamine (DA) transporter ligand 4-[2-[bis(4-fluorophenyl)-methoxy]ethyl]-1-(3-phenylpropyl)piperidine, 1b, were made and biologically evaluated for their binding at the DA and serotonin (5HT) transporters in rat striatal membranes. Different alkyl chain lengths and substitutions were introduced in these molecules to generate an optimum activity and selectivity for the DA transporter. In general, unsubstituted and fluoro-substituted compounds were the most active and selective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 43 publications
(101 reference statements)
5
67
1
Order By: Relevance
“…In contrast, for (ϩ)-2-carbomethoxy-benztropine compounds, replacement of the tropane nitrogen with an oxygen markedly reduced DAT-binding affinity (Meltzer et al, 1997), complementing our findings that the benztropine compounds also require a basic nitrogen for high-affinity binding to DAT (Agoston et al, 1997a). Although a non-nitrogenous analog of GBR 12909 has not been reported, it has been found that one but not the other terminal piperazine nitrogen could be replaced with a methine group without significant diminution of DAT-binding affinity (Dutta et al, 1993(Dutta et al, , 1996. The required nitrogen on which the propylphenyl side chain is attached is analogous to the tropane nitrogen in our benztropine series.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, for (ϩ)-2-carbomethoxy-benztropine compounds, replacement of the tropane nitrogen with an oxygen markedly reduced DAT-binding affinity (Meltzer et al, 1997), complementing our findings that the benztropine compounds also require a basic nitrogen for high-affinity binding to DAT (Agoston et al, 1997a). Although a non-nitrogenous analog of GBR 12909 has not been reported, it has been found that one but not the other terminal piperazine nitrogen could be replaced with a methine group without significant diminution of DAT-binding affinity (Dutta et al, 1993(Dutta et al, , 1996. The required nitrogen on which the propylphenyl side chain is attached is analogous to the tropane nitrogen in our benztropine series.…”
Section: Discussionsupporting
confidence: 83%
“…110 Expansion of the piperidine analogue series has led to some potent DAT ligands that show some divergence from the structure-activity relationships derived from the piperazinyl GBR 12909 analogues. [112][113][114] In particular, the terminal N-benzyl-piperidine analogue is equipotent to GBR 12909, whereas the N-benzyl analogue of GBR 12909 is 17-fold less potent in inhibiting dopamine uptake than the parent drug. Interestingly, the 3,4-dichloro-substituted benzyl piperidine analogue displayed lower affinity at DAT, but significant selectivity over SERT.…”
Section: Gbr 12909 and Its Analoguesmentioning
confidence: 99%
“…3,[12][13][14][15][16] In our initial series of rimcazole analogues, the most potent DAT inhibitor, 1 (K i ) 61 nM), showed moderately potent σ 1 binding affinity (K i ) 97 nM) and was ∼3-fold less potent at SERT (K i ) 219 nM) and 60-fold selective over NET. 11 Several rimcazole analogues (1-4) were evaluated in animal models of cocaine abuse and toxicity.…”
Section: Introductionmentioning
confidence: 99%